Selama Era Pandemi Covid-19, Bagaimana Puskesmas Mertoyudan 1 Melaksanakan PHBS? - Sintia Mashitoh; Septo Pawelas Arso; Nurhasmadiar Nandini (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
ABSTRAKLatar belakang: Selama dua tahun berturut turut pada tahun 2017 dan 2018 Kabupaten Magelang menjadi kabupaten/kota yang memiliki presentase rumah tangga sehat terrendah di Provinsi Jawa Tengah dengan presentase 59.69%. Puskesmas Mertoyudan 1 merupakan puskesmas di Kecamatan Mertoyudan yang memiliki PHBS tatanan Rumah Tangga cukup baik. Namun terdapat dua indikator penilaian yang tergolong masih rendah serta cakupan pendataan rumah sehat yang belum maksimal yakni indikator aktivitas fisik dan tidak merokok dengan presentase masing masing 53.7% dan 42.0%. Selain itu, Puskesmas Mertoyudan 1 merupakan puskesmas dengan kasus konfirmasi Covid-19 yang tinggi. Dari hal tersebut maka diperlukan evaluasi mengenai bagaimana pelaksanaan PHBS rumah tangga pada masa pandemi Covid-19 dari aspek konteks, aspek input, aspek proses dan aspek produk.Metode: Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif menggunakan metode indepth interview yang dipilih berdasarkan Teknik purposive sampling. Subjek penelitian merupakan Kepala Puskesmas, Koordinator Program PHBS dan Kader Kesehatan sebagai informan utama. Sedangkan informan triangulasi yaitu Penanggung Jawab Program PHBS Dinas Kesehatan Kabupaten Magelang dan Masyarakat. Aspek yang dianalisis terdiri dari aspek konteks, aspek input, aspek proses dan aspek produk.Hasil: Hasil penelitian menunjukkan proses pelaksanaan masih mengalami beberapa kendala. Pada aspek konteks, masih terdapat kendala kurangnya kesadaran masyarakat, pada aspek input masih terdapat kendala pada jadwal pelaksanaan, jumlah dan kompetensi tenaga PHBS, pada aspek proses mengalami kendala pada proses pendataan, perencanaan, dan pelaksanaan.Simpulan: Pelaksanaan PHBS pada masa pandemi Covid-19 di Puskesmas Mertoyudan 1 belum berjalan dengan maksimal karena terkendala dengan situasi dan kondisi pandemi yang membatasi kegiatan lapangan. Hal tersebut dipengaruhi oleh beberapa faktor antara lain aspek konteks, aspek input, aspek porses dan aspek produk.Kata kunci: PHBS, Covid-19, Evaluasi, Kabupaten Magelang ABSTRACTTitle: Analysis of the Implementation of the Clean and Healthy Behavior Program (PHBS) at Mertoyudan 1 Public Health Center, Magelang Regency during the Covid-19 Pandemic PeriodBackground: For two consecutive years in 2017 and 2018 Magelang Regency became the district/city that had the lowest percentage of healthy households in Central Java Province with a percentage of 59.69%. Mertoyudan 1 Public Health Center is a health center in Mertoyudan District which has a fairly good PHBS household arrangement. However, there are two assessment indicators that are still low and the coverage of healthy home data collection is not maximized, namely indicators of physical activity and not smoking with a percentage of 53.7% and 42.0%, respectively. Based on data obtained from the Mertoyudan 1 Health Center in 2019, there were 12,893 households that should have been included in the household PHBS data collection, but only 7,454 households were recorded. That means that there are still 42.2% of households that have not been recorded. Based on data obtained from the Magelang District Health Office on November 25, 2020, it is known that Mertoyudan District is the sub-district with the highest confirmed COVID-19 cases in Magelang Regency with details of 166 people confirmed to have recovered, 13 people confirmed dead, 98 people confirmed isolation and 10 people. confirmed to be treated. PHBS activities during the COVID-19 pandemic have not been carried out as well as before the pandemic. High-risk activities allow the spread of COVID-19 such as house-to-house data collection and activities that involve large numbers of people. From this, it is necessary to evaluate how to implement household PHBS during the Covid-19 pandemic from the context aspect, input aspect, process aspect and product aspect.Method: This research was a qualitative research with a descriptive approach using in-depth interview method which is selected based on purposive sampling technique. The research subjects were the Head of the Puskesmas, the PHBS Program Coordinator and the Health Cadre as the main informants. Meanwhile, the triangulation informants were the person in charge of the PHBS program at the Magelang regency health office and the community. The aspects analyzed consist of context aspects, input aspects, process aspects and product aspects.Result: The results of the study show that the implementation process is still experiencing several obstacles. In the context aspect, there are still obstacles to the lack of public awareness, in the input aspect there are still obstacles in the implementation schedule, the number and competence of PHBS staff, in the process aspect there are obstacles in the data collection, planning, and implementation processes.Conclusion: The implementation of PHBS during the Covid-19 pandemic at the Mertoyudan 1 Puskesmas has not run optimally because it is constrained by the pandemic situation and conditions that limit field activities. This is influenced by several factors including context aspects, input aspects, processing aspects and product aspects.Keywords: PHBS, Covid-19, Evaluation, Magelang Recency